Proof of Concept Study: Mesoporous Silica Nanoparticles, From Synthesis to Active Specific Immunotherapy - Seré, Stephanie; Vounckx, Ulrique; Seo, Jin Won; Lenaerts, Ilse; Van Gool, Stefaan; Locquet, Jean-Pierre (Frontiers in Nanotechnology, 2020)
Nanomaterials are increasingly valued tools in drug delivery research as they offer enhanced stability, controlled release and more effective drug encapsulation. Though yet to be introduced in clinical trial, mesoporous silica nanoparticles are promising delivery systems, due to their high chemical and mechanical stability while remaining biodegradable. This work provides proof of concept for particle based vaccines as cost-effective alternatives for dendritic cell immunotherapy. Synthesis and surface chemistry of the nanoparticles are optimized for protein conjugation and nanoparticles are characterized for their physicochemical properties and biodegradation. Ovalbumin is used as a model protein to load nanoparticles to produce a nanovaccine. The vaccine is tested in vitro on dendritic cultures to verify particle and vaccine uptake, toxicity, maturation effects and explicitly ovalbumin cross-presentation on MHC class I molecules. The optimized synthesis protocol renders reproducible mesoporous silica nanoparticles, resistant against agglomeration, within the required size range and have carboxylic surface functionalization necessary for protein conjugation. They are biodegradable over a time span of one week. This period is adjustable by changing synthesis parameters. UV sterilization of the particles does not induce quality loss, nor does it have toxic effects on cells. Treatment with mesoporous silica nanoparticles increases expression of MHC and costimulatory molecules of dendritic cells, indicating an adjuvant effect of nanoparticles on the adaptive immune system. Nanovaccine uptake and cross-presentation of ovalbumin are observed and the latter is increased when delivered by nanoparticles as compared to control conditions. This confirms the large potential of mesoporous silica nanoparticle based vaccines to replace dendritic-based active specific immunotherapy, offering a more standardized production process and higher efficacy.